Efeito do tratamento da palhada, adubação potássica e aplicação de fungicida no rendimento e na incidência de grãos ardidos em milho - Leite, Max Sandro Bezerra (2021)
Burnt grains are among the biotic factors that limit corn (Zea mays L.) productivity, and the occurrence of these diseases has been increasing in corn second crop. The objective of this work was to verify the influence of straw treatment, potassium fertilization and fungicide application on the incidence of burnt grains in corn crop. The experiment was conducted at Bayer's research station, in Sorriso-MT, in the 2019/2020 agricultural year. The experimental design was randomized blocks, arranged in a 2 x 2 x 3 factorial scheme, with subdivided plots arranged in strips (12 lines x 0.5 m between lines x 100 meters) with 10 subplots. DKB390PRO2 was the hybrid used in conducting the trial. The inoculation of Stenocarpella macrospora, was with the inoculum in corn bran, applied in the "cartridge" of the plants in the 4 central lines of each 100-meter plot, during the vegetative stage of the culture (V6, corn with 6 developed leaves). Two fungal treatments were tested, in addition to the control, subdivided into 4 blocks (2 treatments in straw in combination with 2 fertilizations). Data were subjected to analysis of variance (p < 0.05) and treatment means compared by Tukey test (p < 0.05). The estimated leaf severity of S. macrospora was quantified 21 days after inoculations. The fungicides differed significantly from the control treatment. In the application in V8 (maize with 8 developed leaves), VT (bracing) and R2 (corn starting the formation of milky grain) the average control of burned grains was 63.41% for the incidence of ears with burned grains, 64.71% for leaf severity of S. macrospora and 50.61% for grain severity. The application of quaternary ammonia in the straw controls, on average, 31.82% of the leaf severity of S. macrospora, while increasing fertilization reduces 20.92% the incidence of burnt grains in the ear. The application of fungicide significantly reduces the incidence of burnt ears, leaf severity of S. macrospora and burnt grains, being the best control among the tested treatments, followed by more balanced fertilization between nitrogen and potassium.